Test sample and preparation method thereof
By forming an intermediate layer and organic material layer on the surface of the sample, the problem of easily rupture of the sample in the grinding process is solved, the sample is anti -rupture intensity, and the success of the electrical test is ensured.
Patent Information
- Application Number
- CN202310890800.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-19
AI Technical Summary
In the prior art, samples are prone to rupture during grinding, resulting in electrical testing being unable to be performed.
By forming an intermediate layer and an organic material layer on the surface of the initial sample, the intermediate layer is located between the organic material layer and the initial sample, the thickness of the organic material layer is greater than the thickness of the intermediate layer, and the sample is ground using grinding equipment to form an inclined cross-section. test samples.
It improves the rupture resistance of the sample, reduces the risk of rupture during grinding, and ensures the success of subsequent electrical tests.
Smart Images

Figure CN119334711A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor technology, and in particular to a test sample and a preparation method thereof, and a method for monitoring a drain doping region of a power transistor. Background Art
[0002] In the semiconductor field, ion implantation is one of the important process steps. Ion-doped regions are formed through the ion implantation process. The formed ion-doped regions can constitute the well regions, source / drain regions, or other functional doped regions of the device. Therefore, the distribution and concentration of the ion-doped regions will affect the performance of the device. Therefore, it is necessary to test the ion-doped regions.
[0003] In the prior art, a spreading resistance profiler (SRP) is generally used to perform electrical testing on the ion-doped area. Before the electrical test, the sample to be tested needs to be ground so that the sample has an inclined cross-section exposing the ion-doped area, so that the spreading resistance profiler can perform electrical testing based on the inclined cross-section.
[0004] For example Figure 1 As shown, a sample can be ground using a grinding device. The grinding head 10 of the grinding device has an angle gauge at a predetermined angle to the horizontal plane, and the sample 40 is attached to the angle gauge of the grinding head 10. During grinding, the weight of the grinding head 10 and the grinding base 20 presses the sample 40 against the grinding table 30, thereby grinding the sample 40 to form an inclined cross-section for testing. However, during grinding, the sample 40 often breaks, rendering the current sample scrapped and unable to continue subsequent electrical testing. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing a test sample, thereby improving the anti-fracture strength of the sample and alleviating the problem that the sample is prone to fracture during the grinding process.
[0006] The present invention provides a method for preparing a test sample, comprising: providing an initial sample, wherein the initial sample is formed with an ion-doped region, and defining a surface of the initial sample close to the ion-doped region as a predetermined surface; sequentially forming an intermediate layer and an organic material layer on the predetermined surface of the initial sample, wherein the intermediate layer is located between the organic material layer and the initial sample, and the thickness of the organic material layer is greater than the thickness of the intermediate layer; and placing the initial sample on a grinding device so that the organic material layer is inclined in a direction toward a grinding table, and grinding the initial sample using the grinding table to form a test sample with an inclined cross-section.
[0007] Optionally, the intermediate layer is an insulating material layer, and the intermediate layer can be formed by, for example, a thin film deposition process.
[0008] Optionally, the material of the intermediate layer includes at least one of silicon oxide, silicon oxynitride, hafnium oxide and aluminum oxide; and / or, the intermediate layer is formed by an atomic layer deposition process.
[0009] Optionally, the organic material layer is a resin material layer.
[0010] Optionally, the method for preparing the organic material layer includes: coating an organic coating on the intermediate layer; and heating the sample to solidify the organic coating to form the organic material layer.
[0011] Optionally, the thickness of the organic material layer is greater than or equal to 0.5 mm, and the thickness of the intermediate layer is, for example, 2 nm to 10 nm.
[0012] Optionally, the method for obtaining the initial sample includes: cutting a semiconductor substrate to obtain the initial sample.
[0013] The present invention also provides a test sample for performing a spreading resistance test, comprising: a substrate having an ion-doped region formed therein; and an intermediate layer and an organic material layer sequentially formed on the substrate. The test sample has an inclined cross-section that exposes the organic material layer, the intermediate layer, and the ion-doped region.
[0014] Optionally, the material of the intermediate layer includes at least one of silicon oxide, silicon oxynitride, hafnium oxide and aluminum oxide; and / or the thickness of the intermediate layer is 2 nm-10 nm.
[0015] Optionally, the organic material layer is a resin material layer; and / or the thickness of the organic material layer is greater than or equal to 0.5 mm.
[0016] On the other hand, the present invention also provides a method for detecting the drain doping region of a power transistor, comprising: providing a semiconductor substrate on which a power transistor is formed, the drain doping region of the power transistor being formed on the back side of the semiconductor substrate, and cutting the semiconductor substrate to obtain an initial sample; using the preparation method as described above, processing the initial sample to obtain a test sample having an inclined cross-section; and performing a resistance expansion test on the test sample to obtain parameter characteristics of the drain doping region.
[0017] Optionally, a back metal layer is formed on the back side of the semiconductor substrate; and after cutting the semiconductor substrate to obtain the initial sample, the back metal layer is removed.
[0018] In the method for preparing the test sample provided by the present invention, an intermediate layer is formed between the initial sample and the organic material layer to prevent the organic material layer from being directly formed on the initial sample, thereby effectively alleviating the problem of cracks easily generated between the organic material layer and the initial sample due to stress mismatch, improving the adhesion performance between the various film layers on the initial sample, allowing the organic material layer to be formed on the initial sample, and more conducive to increasing the overall thickness of the sample. In addition, the organic material layer is formed on the initial sample, and it is easier to prepare a thicker organic material layer using existing processes, so that the sample can quickly reach a sufficiently large thickness, improving the problem of the sample being easily broken during the grinding process due to its excessively thin thickness. In addition, the organic material layer has strong anti-fracture performance, so it can better withstand the grinding pressure during grinding (especially in the initial stage of grinding), further reducing the risk of the sample breaking during the grinding process.
[0019] When the above-described preparation method is applied to the sample preparation process for testing the drain-doped region of a power transistor, the success rate of preparing test samples containing the drain-doped region can be correspondingly improved, ensuring that subsequent electrical testing can be performed. In particular, for test samples of the drain-doped region of a power transistor, the initially obtained samples are often thin and have a roughened surface. Optimizing this with the preparation method provided by the present invention significantly reduces the risk of sample cracking during the grinding process. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the structure of using grinding equipment to grind the sample to obtain an inclined cross-section.
[0021] Figure 2 This is a flow chart of the preparation of test samples provided in one embodiment of the present invention.
[0022] Figure 3 This is a schematic structural diagram of a sample before grinding in one embodiment of the present invention.
[0023] Figure 4 This is a schematic diagram of the structure after the sample is ground in one embodiment of the present invention.
[0024] Figure 5 This is one of the preparation processes for the test sample provided in one embodiment of the present invention.
[0025] The accompanying drawings are numerals as follows:
[0026] 10- grinding head;
[0027] 20-grinding seat;
[0028] 30-grinding table;
[0029] 40-samples;
[0030] 100 - initial sample;
[0031] 110-substrate;
[0032] 120-ion doping region;
[0033] 210-middle layer;
[0034] 220 - Organic material layer. DETAILED DESCRIPTION
[0035] As described in the background art, when preparing test samples, the samples often break during the grinding process, making subsequent electrical testing impossible. One solution is to manually lift the grinding seat upward based on experience to prevent all gravity from acting on the sample. However, this method is unstable and still difficult to prevent sample breakage even for thinner samples. Another solution is to manually attach a gasket of a certain thickness to the surface of the sample to increase the mechanical strength of the sample. However, it is difficult to keep the gasket completely horizontal when manually attaching the gasket, and grinding in this case will still cause the sample to break.
[0036] In this regard, the present invention provides another solution, which is to optimize the sample preparation method to improve the problem that the sample is prone to fragmentation during the grinding process. Figure 2 As shown, a method for preparing a test sample provided in one embodiment of the present invention may include the following steps.
[0037] In step S100 , an initial sample is provided, wherein an ion-doped region is formed on the initial sample, and a surface of the initial sample close to the ion-doped region is defined as a predetermined surface.
[0038] In step S200 , an intermediate layer and an organic material layer are sequentially formed on a predetermined surface of the initial sample, wherein the intermediate layer is located between the organic material layer and the initial sample, and the thickness of the organic material layer is greater than that of the intermediate layer.
[0039] Step S300 : placing the initial sample on a grinding device so that the organic material layer is tilted toward a grinding table, and grinding the initial sample using the grinding table to form a test sample with an inclined cross section.
[0040] The test sample preparation method provided by the present invention forms an intermediate layer on the surface of the initial sample, thereby avoiding the problem of cracks caused by poor adhesion between the organic material layer and the initial sample due to direct formation of the organic material layer. Furthermore, by forming the organic material layer on the initial sample, the thickness of the sample is increased, thereby improving the sample's crack resistance. This allows the sample to better withstand the pressure and grinding stress applied by the grinding equipment during the subsequent grinding process, thereby alleviating the problem of sample cracking.
[0041] The test sample and preparation method thereof proposed in the present invention are further described in detail below with reference to the accompanying drawings and specific embodiments. The advantages and features of the present invention will become clearer based on the following description. It should be noted that the drawings are all in a very simplified form and are not in precise proportions, and are only used to conveniently and clearly assist in illustrating the purpose of the embodiments of the present invention. It should be recognized that relative terms such as "above", "below", "top", "bottom", "above" and "below" shown in the drawings can be used to describe the relationship between various elements. These relative terms are intended to cover different orientations of elements other than the orientations depicted in the drawings. For example, if the device is inverted relative to the view in the drawing, an element described as being "above" another element would now be below that element.
[0042] The following combination Figure 2 as well as Figure 3-Figure 4 The various steps of preparing the test sample provided in this embodiment are described, wherein Figure 3 This is a schematic diagram of the structure before grinding the sample in one embodiment of the present invention. Figure 4 This is a schematic diagram of the structure after the sample is ground in one embodiment of the present invention.
[0043] In step S100, an initial sample 100 is provided, wherein an ion doping region 120 is formed in the initial sample 100. For example, Figure 3 As shown, the initial sample 100 may specifically include a substrate 110 and an ion doping region 120 formed in the substrate 110 .
[0044] The surface of the initial sample 100 that is closer to the ion-doped region 120 can be defined as a predetermined surface. When the inclined surface is subsequently ground, the predetermined surface is tilted toward the grinding table. Specifically, the initial sample 100 has a first surface and a second surface that are opposed to each other. The ion-doped region 120 is closer to the first surface. When the sample is ground, the first surface is tilted toward the grinding table to facilitate faster and more complete exposure of the inclined cross-section of the ion-doped region 120 within the initial sample 100.
[0045] Furthermore, the initial sample 100 can be specifically cut from a semiconductor substrate (e.g., a wafer). The semiconductor substrate is, for example, a thinned semiconductor substrate, and the thickness of the thinned semiconductor substrate is, for example, 90 μm-150 μm. That is, the thickness of the thinned semiconductor substrate is very thin, and accordingly, the thickness of the initial sample 100 obtained by cutting is also very thin (e.g., 90 μm-150 μm). At this time, if the initial sample 100 is directly ground, it will easily cause the sample to break. Therefore, it is necessary to further process the ultra-thin sample obtained by cutting to improve its anti-fracture ability. In addition, the initial sample 100 obtained by cutting can be a rectangular block, and its length dimension is, for example, 0.5 cm-2 cm, and its width dimension is, for example, 0.1 cm-0.8 cm.
[0046] In practical applications, the initial sample 100 is obtained by, for example, cutting from a semiconductor substrate on which a power transistor is formed. Specifically, the power transistor is, for example, an insulated gate field effect transistor (IGBT) or a shielded gate field effect transistor (SGT), and ion implantation is performed on the back side of the semiconductor substrate to form a drain doping region of the power transistor. Therefore, in the initial sample 100 obtained by cutting the semiconductor substrate, the ion doping region 120 thereof corresponds to the drain doping region of the power transistor. By performing parameter detection on the ion doping region 120 (for example, including detection of parameters such as the distribution and / or concentration of the ion doping region 120), the parameters of the drain doping region of the power transistor can be reflected.
[0047] In addition, for a semiconductor substrate having a power transistor formed thereon, the processing process also includes: forming a back metal layer on the back side of the semiconductor substrate, the back metal layer being electrically connected to the drain doping region. At this time, in order to improve the adhesion performance of the back metal layer on the semiconductor substrate, the back side of the semiconductor substrate may be roughened before the back metal layer is formed, for example, the roughness of the back side of the semiconductor substrate may be increased by wet etching. However, the roughened initial sample 100 obtained by cutting from the roughened semiconductor substrate is more likely to break during the subsequent grinding of the bevel. To this end, in this embodiment, an intermediate layer 210 and an organic material layer 220 are formed on the surface of the initial sample 100 to greatly reduce the risk of sample breakage. For details, please refer to step S200 below.
[0048] In step S200, continue to refer to Figure 3 As shown, the intermediate layer 210 and the organic material layer 220 are sequentially formed on a predetermined surface of the initial sample 100 , and the thickness of the organic material layer 220 is greater than that of the intermediate layer 210 .
[0049] The intermediate layer 210 is positioned between the organic material layer 220 and the initial sample 100 to prevent the organic material layer 220 from being formed directly on the initial sample 100, which could lead to cracks due to poor adhesion between the two. Specifically, if the intermediate layer 210 is not provided between the initial sample 100 and the organic material layer 220, and the organic material layer 220 is formed directly on the initial sample 100, the significant difference in stress between the organic material layer 220 and the initial sample 100 could easily lead to poor adhesion between the organic material layer 220 and the sample surface, resulting in cracks. This could result in the prepared sample failing to meet testing requirements. In particular, the thickness of the organic material layer 220 in this embodiment is relatively large, which is conducive to significantly increasing the overall thickness of the sample. However, the thicker organic material layer 220 is more likely to have cracks between it and the initial sample 100 due to stress mismatch. To this end, in this embodiment, an intermediate layer 210 is provided. The stress of the intermediate layer 210 is closer to the surface stress of the initial sample 100 relative to the organic material layer 220, thereby effectively alleviating the problem of cracks between the organic material layer 220 and the initial sample 100 due to stress mismatch, improving the adhesion performance between the various film layers on the initial sample 100, and making the final test sample meet the requirements of subsequent electrical testing.
[0050] Therefore, it can be considered that the intermediate layer 210 constitutes an adhesive layer between the organic material layer 220 and the initial sample 100, thereby improving the adhesion strength of the organic material layer 220 on the initial sample 100. It can also be considered that the intermediate layer 210 constitutes a buffer layer between the organic material layer 220 and the initial sample 100, which effectively alleviates the stress difference between the organic material layer 220 and the initial sample 100, thereby improving the problem of cracks easily generated between the organic material layer 220 and the initial sample 100 due to stress mismatch.
[0051] Furthermore, the intermediate layer 210 is specifically an insulating material layer, and its insulating material includes, for example, at least one of silicon oxide, silicon oxynitride, hafnium oxide, and aluminum oxide. Taking the initial sample of the silicon-based wafer as an example, an intermediate layer 210 of silicon oxide material can be used at this time. Due to the good stress matching between the silicon oxide material and the silicon-based material, the silicon oxide material has high adhesion to the silicon-based material. In addition, the intermediate layer 210 is formed of an insulating material, so that when the electrical test is performed later, the two probes of the extended resistance tester are simultaneously inserted into the intermediate layer 210 without short circuiting, thereby preventing the probes from burning.
[0052] In a specific example, the intermediate layer 210 can be formed using a thin film deposition process, for example. The intermediate layer 210 thus formed has good coverage and flatness, so that while the intermediate layer 210 is used to improve the adhesion of the organic material layer 220 on the initial sample 100, it can ensure the levelness of the sample surface and reduce the risk of the sample breaking due to poor surface levelness during subsequent grinding. In a specific example, the intermediate layer 210 can be formed using an atomic layer deposition process (ALD) to improve the uniformity of coverage of the intermediate layer 210 on the sample surface, especially to form an intermediate layer 210 with a smaller thickness. The intermediate layer 210 with a smaller thickness can still evenly cover the entire sample surface. For example, the thickness of the intermediate layer 210 can be set to 2nm-10nm.
[0053] As described above, in this embodiment, a relatively thick organic material layer 220 is formed on the initial sample 100 to increase the overall thickness of the sample, thereby improving the mechanical strength of the sample. This allows the sample to better withstand the pressure and grinding stress applied by the grinding equipment during the subsequent grinding process, thereby alleviating the problem of the sample being prone to cracking during the grinding process. The thickness of the organic material layer 220 can be, for example, greater than or equal to 1000 times the thickness of the intermediate layer 210, and can even be greater than or equal to the thickness of the initial sample 100. For example, the thickness of the organic material layer 220 can be greater than or equal to 500 μm, or can further be greater than or equal to 1000 μm.
[0054] Furthermore, the organic material layer 220 can be formed, for example, using a coating process, enabling the rapid and efficient production of a thick organic coating. Specifically, the method for preparing the organic material layer 220 includes: first, coating the intermediate layer 210 with an organic material, such as AB glue (where A:B = 1:1); then, heating the sample to solidify the organic material to form the organic material layer 220. In a specific example, the sample can be placed in a temperature environment of 120°-180° and heated for 15-30 minutes. It should be noted that in this embodiment, coating the organic material layer 220 on the intermediate layer 210 during heating to solidify the organic coating overcomes the problem of cracks in the solidified organic material layer 220 on the sample surface due to the significant difference in surface tension between the organic coating and the initial sample 100. In other words, in this embodiment, the intermediate layer 210 is used to buffer the stress difference between the organic material layer 220 and the sample, effectively alleviating the phenomenon of cracks between the various film layers due to stress differences, thereby improving the adhesion between the various film layers.
[0055] In step S300, refer to Figure 4As shown, the initial sample 100 is set in a direction with its predetermined surface inclined toward the grinding table, that is, the organic material layer on the initial sample is inclined toward the grinding table, and the sample is ground using the grinding table to form a test sample 100' with an inclined cross-section.
[0056] In one example, one can use, for example Figure 1 Specifically, the sample is adhered to the angle gauge of the grinding head 10, and the grinding head 10 with the sample adhered is installed on the grinding seat 20. Then, under the pressure of the grinding head 10 and the grinding seat 20, the sample is pressed against the grinding table 30, so that the sample is ground using the grinding table 30, and the grinding table 30 is, for example, a frosted glass disk. It should be noted that, compared with the initial sample without forming an organic material layer, in this embodiment, since the organic material layer 220 is provided, in the initial stage of grinding, the organic material layer 220 on the sample can replace the initial sample 100 and preferentially press against the grinding table 30 to withstand the grinding pressure in the initial stage. In addition, the organic material has good anti-fracture strength, which effectively improves the problem of sample fracture during the grinding process.
[0057] The following is a specific example to illustrate the preparation process of the test sample provided in this embodiment. Figure 5 As shown, a method for preparing a test sample for a resistance expansion test includes:
[0058] First, the semiconductor substrate is cut to obtain an initial sample in a rectangular shape, for example, wherein the length of the initial sample is, for example, 0.5 cm to 2 cm, and the width is, for example, 0.1 cm to 0.8 cm;
[0059] Then, an intermediate layer (e.g. Figure 3 The intermediate layer 210 shown in FIG. 2 includes, for example, at least one of a silicon oxide layer, a silicon oxynitride layer, a hafnium oxide layer, and an aluminum oxide layer, and has a thickness of, for example, 2 nm to 10 nm. The process temperature in the atomic layer deposition process is, for example, 30° C. to 50° C., and the deposition time is, for example, 15 min to 20 min.
[0060] Next, an organic coating is coated on the intermediate layer 210 , and the organic coating is, for example, AB glue;
[0061] Next, the sample is heated to solidify the organic coating to form an organic material layer (eg Figure 3 The organic material layer 220 shown in the figure is heated at a temperature of, for example, 120° C. to 180° C. and for a heating time of, for example, 15 min to 25 min.
[0062] Next, the sample is attached to a grinding device, such as the one described in the previous section. Figure 1 As shown, paraffin wax can be used to adhere the sample to the angle gauge of the grinding head 10;
[0063] Next, continue to refer to Figure 1 As shown, the grinding head 10 is loaded on the grinding seat 20 to grind the sample, thereby forming a test sample with an inclined cross section;
[0064] Afterwards, the resistance expansion test can be performed on the test sample.
[0065] Based on the preparation method of the test sample described above, this embodiment also provides a test sample that can be used to perform a resistance expansion test. Figure 4 As shown, the test sample 100' includes: a substrate 110, in which an ion-doped region 120 is formed; and an intermediate layer 210 and an organic material layer 220 sequentially formed on the substrate 110. The test sample 100' also has an inclined cross-section that exposes the organic material layer 220, the intermediate layer 210, and the ion-doped region 120.
[0066] In the test sample 100', the intermediate layer 210 can be used to improve the adhesion of the organic material layer 220 to the substrate 110, thereby avoiding cracks between the organic material layer 220 and the substrate 110 due to poor adhesion. Furthermore, the intermediate layer 210 can be an insulating material layer, such as at least one of silicon oxide, silicon oxynitride, hafnium oxide, and aluminum oxide. Furthermore, the intermediate layer 210 can be formed using an atomic layer deposition process, which helps improve the film uniformity of the intermediate layer 210. Even if the intermediate layer 210 is relatively thin, it can still uniformly cover the surface of the substrate 110. Based on this, the thickness of the intermediate layer 210 can be controlled within a relatively small range (for example, the thickness of the intermediate layer 210 can be controlled within 2 nm to 10 nm), reducing the time required for thin film deposition and thereby improving sample preparation efficiency.
[0067] In the test sample 100' provided in this embodiment, a thicker organic material layer 220 is formed to increase the overall thickness of the sample, improving its mechanical strength. Furthermore, the organic material layer 220 has strong crack resistance, thus better protecting the sample and ensuring that the test sample 100' meets the requirements of the spreading resistance test. Specifically, the organic material layer can be a resin layer (e.g., AB glue) and can be 0.5 mm or thicker.
[0068] After the test sample 100 ′ is prepared, an electrical test can be performed using a resistance expansion tester to obtain parameter characteristics of the ion-doped region 120 .
[0069] With respect to the test sample and its preparation method provided in this embodiment, the specific application thereof in actual scenarios is described in detail below. Taking the detection of the drain doping region of a power transistor as an example, the specific detection method includes: first, providing a semiconductor substrate on which a power transistor is formed, the power transistor being, for example, an insulated gate field effect transistor (IGBT) or a shielded gate field effect transistor (SGT), and the back side of the semiconductor substrate being formed with the drain doping region of the power transistor; then, cutting the semiconductor substrate to obtain an initial sample; then, processing the initial sample using the test sample preparation method described above to obtain a test sample having an inclined cross section, the inclined cross section obliquely exposing the drain doping region; thereafter, performing a resistance extension test on the test sample to obtain parameter characteristics of the drain doping region, such as obtaining the doping depth and / or ion concentration of the drain doping region.
[0070] In an optional solution, the back side of the semiconductor substrate is a roughened surface, and a back metal layer is also formed on the back side of the semiconductor substrate, which is electrically connected to the drain doped region. Based on this, after cutting the semiconductor substrate to obtain the initial sample, the back metal layer is removed so that the intermediate layer and the organic material layer are sequentially formed on the surface after the back metal layer is removed. This avoids the problem of the metal layer being exposed on the inclined cross section formed by subsequent grinding, preventing the two probes of the diffusion resistance tester from contacting the metal layer at the same time and causing a short circuit.
[0071] It should be noted that although the present invention has been disclosed above with reference to preferred embodiments, the above embodiments are not intended to limit the present invention. For any person skilled in the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or to modify it into an equivalent embodiment with equivalent changes. Therefore, any simple modification, equivalent change, and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of protection of the technical solution of the present invention.
[0072] It should also be understood that as used herein and in the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly indicates otherwise. For example, reference to "a step" or "a device" means reference to one or more steps or devices and may include subsequent steps and devices. All conjunctions used should be interpreted in their broadest sense. Furthermore, the word "or" should be interpreted as having the definition of a logical "or," not a logical "exclusive or," unless the context clearly indicates otherwise.
Claims
1. A method for preparing a test sample, characterized in that: include: Providing an initial sample, wherein the initial sample is formed with an ion-doped region, and defining a surface of the initial sample close to the ion-doped region as a predetermined surface; forming an intermediate layer and an organic material layer in sequence on a predetermined surface of the initial sample, wherein the intermediate layer is located between the organic material layer and the initial sample, and the thickness of the organic material layer is greater than the thickness of the intermediate layer; as well as, The initial sample is placed on a grinding device so that the organic material layer is inclined in a direction toward a grinding table, and the initial sample is ground using the grinding table to form a test sample with an inclined cross section.
2. The method for preparing a test sample according to claim 1, wherein: The middle layer is an insulating material layer.
3. The method for preparing a test sample according to claim 1, wherein: The intermediate layer is formed by a thin film deposition process.
4. The method for preparing a test sample according to claim 2, wherein: The material of the intermediate layer includes at least one of silicon oxide, silicon oxynitride, hafnium oxide and aluminum oxide; and / or the intermediate layer is formed by an atomic layer deposition process.
5. The method for preparing a test sample according to claim 1, wherein: The thickness of the intermediate layer is 2nm-10nm.
6. The method for preparing a test sample according to claim 1, wherein: The organic material layer is a resin material layer.
7. The method for preparing a test sample according to claim 1, wherein: The method for preparing the organic material layer comprises: coating an organic coating on the intermediate layer; and heating the sample to solidify the organic coating to form the organic material layer.
8. The method for preparing a test sample according to claim 1, wherein: The thickness of the organic material layer is greater than or equal to 0.5 mm.
9. The method for preparing a test sample according to claim 1, wherein: The method for obtaining the initial sample includes: cutting a semiconductor substrate to obtain the initial sample.
10. A test sample for performing an extended resistance test, characterized in that: include: A substrate having an ion-doped region formed therein; and, sequentially forming an intermediate layer and an organic material layer on the substrate; The test sample has an inclined cross section, and the inclined cross section exposes the organic material layer, the intermediate layer and the ion-doped region.
11. The test sample according to claim 10, characterized in that The material of the intermediate layer includes at least one of silicon oxide, silicon oxynitride, hafnium oxide and aluminum oxide; and / or the thickness of the intermediate layer is 2nm-10nm.
12. The test sample according to claim 10, characterized in that The organic material layer is a resin material layer; and / or the thickness of the organic material layer is greater than or equal to 0.5 mm.
13. A method for detecting a drain doping region of a power transistor, characterized in that: include: Providing a semiconductor substrate on which a power transistor is formed, wherein a drain doping region of the power transistor is formed on the back side of the semiconductor substrate, and cutting the semiconductor substrate to obtain an initial sample; Using the preparation method according to any one of claims 1 to 8, processing the initial sample to obtain a test sample with an inclined cross section; and A resistance expansion test is performed on the test sample to obtain parameter characteristics of the drain doping region.
14. The method for detecting a drain doping region according to claim 13, wherein: A back metal layer is also formed on the back side of the semiconductor substrate; and after cutting the semiconductor substrate to obtain an initial sample, the back metal layer is removed.
Citation Information
Patent Citations
Method for manufacturing semiconductor device, and polishing apparatus
CN101645398A
Grinding pad, grinding machine table and grinding method
CN103862364A
Preparation method of spreading resistance test sample
CN104810239A
Method for manufacturing semiconductor element
CN115428127A
Semiconductor device
CN1362744A